2018
DOI: 10.1186/s12871-018-0661-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anesthesiologists’ knowledge about occupational health: Pilot study

Abstract: BackgroundAn anesthesiologists’ work presents with numerous occupational risks owing to the large amount of time spent inside the operating room where constant noise, anesthetic vapors, ionizing radiation, infectious agents, and psychological stress are present. Herein, we evaluated anesthesiologists’ knowledge about occupational health.MethodsA cross-sectional study was conducted to assess 158 anesthesiologists from a tertiary hospital on their knowledge about occupational health using a structured questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
4
0
4
Order By: Relevance
“…Fourth, improve anesthesia workers' awareness regarding occupational risks related to their functions to consequently increase adherence and recognition of safety measurements. A pilot study with anesthesiologists revealed a lack of knowledge in major topics of occupational health [87]. In a specific survey on inhaled anesthetics with anesthesiologists and nurse anesthetists, 76% of the participants related to feeling exposed to inhaled anesthetics, however, simple measures for the avoidance of WAGs were not being used [88].…”
Section: Minimizing Exposure To Wagsmentioning
confidence: 99%
“…Fourth, improve anesthesia workers' awareness regarding occupational risks related to their functions to consequently increase adherence and recognition of safety measurements. A pilot study with anesthesiologists revealed a lack of knowledge in major topics of occupational health [87]. In a specific survey on inhaled anesthetics with anesthesiologists and nurse anesthetists, 76% of the participants related to feeling exposed to inhaled anesthetics, however, simple measures for the avoidance of WAGs were not being used [88].…”
Section: Minimizing Exposure To Wagsmentioning
confidence: 99%
“…Yerel Etik Kuruldan "anestezistlerin mesleki riskleri konusundaki bilgilerinin değerlendirilmesi" başlıklı anket çalışması için onay alındı. Örnek bir çalışma temel alınarak, çoktan seçmeli soru tekniği kullanılarak hazırlanan anket, tarafsızlık ve katılımcıların yanıtlarının yönlendirilmemesi ilkesine uygun olarak hazırlandı (1) . Eğitim ve araştırma hastanelerin-de anesteziyoloji ve reanimasyon kliniklerinde çalışan gönüllü asistan ve uzman hekimlerin, basılı anket formlarının dağıtılıp doldurulması yöntemi ile araştırma verileri toplandı.…”
Section: Gereç Ve Yöntemunclassified
“…ve ark. 'nın (1) 3. basamak bir hastanede 158 anestezistin iş sağlığı konusundaki bilgilerini değerlendirdiği kesitsel çalışma temel alınarak yapılandırılmış bir anket kullanıldı. Sorulara verilen doğru yanıt oranları ile hesaplanan etki büyüklüğü (Cohen's d=0.3), alfa hata (p değeri= 0.05) ve 1-beta hata (power) değerinin ise 0.90 olduğu varsayılarak yokluk hipotezinin test edilmesi için çalışmada 117 kişinin yeterli olacağı anlaşıldı.…”
Section: İstatistiksel Analizunclassified
See 2 more Smart Citations